Analisis Numerik Kuat Lentur Elemen Balok T Curved Tile Semi Pracetak Dengan Variasi Mutu Beton Cast In Place - Rian Fajri Ramadanas; Ismeddiyanto Ismeddiyanto; Reni Suryanita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
T beam elements curved tile semi precast is a combination concrete precast with concrete cast in place, which aims to improve the efficiency construction of reinforced concrete structures. Quality concrete cast in place, can be influenced by various factors such as human error, weather and others. Thus the need to be studied further how the influence of variations in the quality of concrete cast in place. The purpose of this study is to analyze the results of the flexural strength T beam semi precast elements, especially against the load-deflection relationship, the moment-curvature, and the pattern of cracks caused. The study used curved tile T beam semi precast element with dimension of 60 cm width, height 18 cm, and a length of 300 cm. Quality of precast concrete is 22 MPa and the quality variations of cast in place concrete were 15 MPa, 19 MPa, 20 MPa, 22 MPa and 25 MPa. The axial load of T beam Model increased, starting from zero up to fail. Base on the finite element analysis software improved, the received axial load greater the 20,51 kN, 21,00 kN, 23,47 kN, 23,67 kN and 23,80 kN. For the moment curvature analysis results, with increases in the quality of concrete, moment that occurs is also increasing the 20,51 kNm, 21,00 kNm, 23,47 kNm, 23,67 kNm and 23,80 kNm. Cracks that occurred on all elements of T semi precast beams are cracked flexural, where the bending moment occurred on the area's largest. Therefore this study can be an additional reference to community and alternative in the manufacture of semi precast T beam element, as well as understanding of the use of computer applications in the identification of mechanical properties of concrete.Keywords: Cast In Place Concrete, Curved tile, Finite Element Analysis Software, Flexural Strength, Concrete Precast, T Beam